Procedures For Buying and Selling and Registration of Land Absentee as an Object of Land Ownership - Muhammad Rifaldi Setiawan; Putri Raodah (JIHAD : Jurnal Ilmu Hukum dan Administrasi, 2026)
This study aims to analyze the procedures for the sale and purchase as well as the registration of absentee land as an object of ownership rights within the framework of Indonesian agrarian law. The issues addressed include the fulfillment of material and formal requirements in land transactions, the role of the Land Deed Official (PPAT), and the mechanism for registering the transfer of land rights. This research employs a normative legal method using both statutory and conceptual approaches. The statutory approach examines relevant regulations, while the conceptual approach explores legal doctrines related to land law, particularly concerning absentee land ownership. The results indicate that the implementation of absentee land transactions must comply with both material and formal requirements. The material requirements concern the legality of the parties and the object of the transaction, where the seller must be the lawful holder of land rights, and the buyer must qualify as a subject of ownership rights without violating the prohibition of absentee land ownership. Meanwhile, the formal requirement is fulfilled through the execution of a Sale and Purchase Deed (AJB) before the Land Deed Official (PPAT), which serves as the legal basis for the registration of the transfer of rights at the Land Office. Land registration plays a crucial role in ensuring legal certainty, legal protection, and orderly land administration. However, in practice, several obstacles remain, including limited public understanding of legal provisions and administrative constraints. Therefore, enhancing legal awareness and strengthening the role of PPAT and land administration institutions are necessary to achieve legal certainty in land transactions.